Diversite Phlebotomienne Dans Trois Villages De La Commune De Bouake (Côte d’Ivoire) Durant La Periode De Mars A Juin 2019 - Nadège, Assovié Koco Rita; Vincent, Djohan; Frédéric, Atta Angui Amoikon; Arnaud, Aké Donald Hermann; Armel, Aka Tigori; Patrice, Akoliba Koliba; Berté, Djakaridja; Dieudonné, Ta Bi Tra; Dramane, Kaba; Grégoire, Yapi Yapi (European Scientific Journal, ESJ, 2020)
Cutaneous leishmaniasis is a parasitosis caused by protozoa of the genus Leishmania and is widespread worldwide. A medical survey carried out in three villages of the city of Bouaké, around suspected cases of cutaneous leishmaniasis, confirmed the presence of this pathology in these villages. As part of the identification of the actors of the epidemiological cycle of cutaneous leishmaniasis, an entomological study was conducted in these villages in order to identify potential phlebotomus vectors of leishmaniasis. Oil traps and CDC light traps were set between March and June 2019, following a rotation method between trapping sites. They were set between 5:00 pm and 6:00 pm and were collected the next morning between 7:00 am and 8:00 am. The specific diversity of the identified species was determined from the ecological indices of equitability and Hill’s ecological indices. These traps allowed the capture of 135 sandfish, 78 of which were morphologically identified. The genus Sergentomyia constituted 91% of our harvests against 9% for the genus Phlebotomus. Ph. bergeroti, Ph. rodhaini and Ph. sergenti were the species of the genus Phlebotomus caught at these sites. Further work on the identification of the parasite in both sandflies and humans should be carried out in order to identify the sandflies incriminated in the transmission of leishmania in Bouaké.